Implementasi Pasal 71 PKPU No. 15 Tahun 2023 tentang Kampanye dalam Perspektif Fiqh Siyasah Tanfidziyah (Studi Bawaslu Bandar Lampung) - Ismed Ananta; Liky Faizal; Dani Amran Hakim (Kartika: Jurnal Studi Keislaman, 2026)
This study stems from academic concerns regarding the continued violation of campaign material regulations during elections, despite the provisions stipulated in Article 71 of General Election Commission Regulation No. 15 of 2023. This situation indicates a gap between legal norms and their implementation in the field, particularly in the supervisory function of the Election Supervisory Agency (Bawaslu). This study aims to analyze the implementation of Article 71 of PKPU Number 15 of 2023 concerning campaign materials in Bandar Lampung City and examine it from the perspective of fiqh siyasah tanfidziyah as a concept of the exercise of governmental power in Islam. This study uses a qualitative method with a juridical-empirical approach through interviews, documentation, and the study of laws and regulations. The results of the study show that the implementation of campaign prop supervision has not been optimal due to limitations in supervision, low compliance among election participants, and coordination factors between institutions. From the perspective of fiqh siyasah tanfidziyah, campaign monitoring is part of the implementation of the government's mandate to maintain justice and public interest. The implications of this study emphasize the importance of strengthening election monitoring based on the values of justice and government accountability